(untitled) (Global Journals of Research in Engineering, 2013)
Solar distillation is a simple treatment of brackish (i.e. contain dissolved salts) water supplies. Distillation is the processes that can be used for water purification and can use any heating source.Solar distillation is used to yield drinking water or to yield pure water for lead acid batteries, hospitals, laboratories and in generating commercial products such as rose water.In this study, a basin type solar still (BSS) is designed, constructed and field experiments have been carried out to check the productivity of the still. The field experiments of the BSS are carried from June 07, 2011 to June 09, 2012. The maximum daily distilled water production is obtained as 3.76 lit/m2-day in July 31, 2011. Also maximum hourly distilled water production is observed as 0.46 lit/m2-hr. The average daily and hourly production rates are found as 1.80 lit/m2-day and 0.20 lit/m2-hr, respectively. The production cost of distilled water is calculated as 0.33 Tk/lit.